Substituting sedentary time with physical activity in youngest-old to oldest-old community-dwelling older adults: Associations with body composition - Lai, Ting-Fu; Liao, Yung; Hsueh, Ming-Chun; Yen, Hsin-Yen; Park, Jong-Hwan; Chang, Jae Hyeok (Frontiers in Public Health, 2022)
Abstract Several studies have suggested that physical activity and sedentary behavior are strongly and independently associated with body composition and obesity. However, few studies have investigated whether substituting sedentary time with moderate-to-vigorous physical activity is associated with body composition in older adults, especially among those older than 75 years. This study examined the associations between replacing sedentary time with physical activity and obesity indices in a sample of 199 community-dwelling older Taiwanese adults (52.3 % women; 80.6 ± 7.0 years). Physical activity and sedentary behavior were measured using the triaxial accelerometer (GT3X+, ActiGraph). Body composition indices were computed through a bioelectrical impedance analysis of body fat percentage and appendicular skeletal muscle mass index. Waist circumference and body mass index were measured by trained personnel. Isotemporal substitution analyses estimated these associations after adjusting for sociodemographic characteristics and nutritional status. The study showed that substituting 30 minutes of sedentary behavior per day with moderate-to-vigorous physical activity was associated with lower body fat percentage (B = -1.408, 95% CI= -2.55, -0.264), body mass index (B= -0.681, 95% CI= -1.300, -0.061), and waist circumference (B = -2.301, 95% CI= -4.062, -0.539) after adjusting for covariates. Substituting 30 minutes of light physical activity per day with moderate-to-vigorous physical activity was associated with lower waist circumference (B = -2.230, 95% CI= -4.173, -0.287) after adjusting for covariates. Stratified analyses indicated that associations were stronger in youngest-old older adults, and in older adults with a normal nutritional status (versus underweight status). These findings confirm the importance of reducing sedentary behavior and increasing moderate-to-vigorous physical activity among older adults to improve their physical health, as well as highlighting the importance of taking into account nutritional status and age group.